Business Plan for a New Vietnamese Restaurant for Diabetic People. Case: Rovaniemi. - Nguyen, Giang (2022)
The thesis discusses building a business plan for a new Vietnamese restaurant in Rovaniemi. The main target group that the restaurant aims at is diabetic people, and people preferring low-carb diets. However, local citizens and tourists are more than welcome at the restaurant. After the Covid pandemic, there are more and more tourists visiting Rovaniemi again, combining with the rise of interest in Southeast Asian cuisine in Finland, the decision to establish a new Vietnamese restaurant is made. The qualitative research of the thesis was conducted as an individual in-depth interview, which was made with one of the owners of another Asian restaurant in Rovaniemi. The purpose of the interview was to use secondary research methods to learn more about the market situation in the area, and the struggle in finance at the beginning of one’s business. General analysis like market study, financial analysis, mission and vision statement, and marketing strategy will be discussed. Moreover, through using business tools such as SWOT analysis, Customer Journey Mapping, and The Business Model Canvas, a complete picture of the business is formulated. The results of the study show that despite being not familiar with Vietnamese food, many Finnish people are willing to step out of their comfort zone and try new dishes. Choosing Rovaniemi as the location for opening a restaurant is a good option despite other disadvantageous elements. Despite facing some challenges and threats, there is a positive future for a new Vietnamese restaurant in town. The results of this paper could be used as a future reference for other people who intend to do business in Rovaniemi.